Photosynthetic characteristics of the subtending leaf of cotton boll at different fruiting branch nodes and their relationships with lint yield and fiber quality - Liu, Jingran; meng, Yali; Lv, Fengjuan; Chen, Ji; Ma, Yina; Wang, Youhua; Chen, Binglin; Zhang, Lei; Zhou, Zhiguo (Frontiers in Plant Science, 2015)
To investigate photosynthetic characteristics of the subtending leaf at the 2-3rd and 10-11th fruiting branch (FBN, FB2-3 and FB10-11), and their relationship with cotton yield and quality, field experiments were conducted using two cotton cultivars, Kemian 1 and Sumian 15. The results showed that with FBN increasing, chlorophyll (Chl) components, Pn and non-photochemical quenching (NPQ) in the subtending leaf significantly declined, while soluble sugar, amino acid and their ratio (CSS/CAA) as well as Fv/Fm increased. These results indicated that 1) non-radiative dissipation of excess light energy at FB2-3 was reduced to improve solar energy utilization efficiency to compensate for lower Pn, 2) higher NPQ at FB10-11 played a role in leaf photo-damage avoidance, 3) boll weight was related to the CSS/CAA ratio rather than carbohydrates content alone, 4) with FBN increasing, lint biomass and lint/seed ratio increased significantly, but lint yield decreased due to lower relative amount of bolls, and 5) the decreases in Pn, sucrose content and CSS/CAA in the subtending leaf at FB2-3 resulted in lower boll weight and fiber strength.